EFFECT OF POLYVINYLPYRROLIDONE ADDITIVE ON MEMBRANE CHARACTERISTICS IN THE PREPARATION OF POLYETHERSULFONE HOLLOW FIBER MEMBRANE - Syahril Ahmad (Jurnal Kimia Terapan Indonesia, 1993)
Preparation by applying the dry - wet spinning method and characterization of polyethersulfone (PES) hollow fiber membranes for ultrafiltration purpose have been studied. The characteristics of the hallow fibers studied include water flux, rejection rate, molecular weight cut - off and cross section structure. The membrane was prepared using the dope solution composition of 20% PES, 6% Polyvinylpyrrolidone (PVP) and 74% of n-Methyl Pyrrolidone as solvent. The effect of molecular weight of PVP and the small amount of water added in the dope solution have also been studied. The results show that increasing the molecular weight of PVP in the dope solution will decrease the rejection coefficient of the membrane towards dextran solution. Effect of a small amount of water in the dope solution as wetting agent is not obvious as indicated by the fluctuations in the results. Higher operating pressure during ultrafiltration process give higher water flux, but the effect on membrane rejection is not clear. By taking the rejection coefficient as 90 %, the molecular weight cut-off of the hallow fiber prepared are 40,000; 80,000; 25,000 and 110,000.